About Argentine women architects, competitions and representation in the press (1947-1967) - Méndez, Patricia (Estoa. Journal of the Faculty of Architecture and Urbanism, 2026)
From a gender perspective, this documentary study systematically analyzes the participation of women architects in architectural design competitions convened by the Central Society of Architects (SCA) between 1947 and 1967. Using a documentary methodology, the official records of the professional association were reviewed and compared with journalistic coverage by the newspaper La Prensa during that period. It was possible to identify awards, as well as paradigmatic cases of their protagonists. The results revealed and made visible nearly two hundred awards won by women in architecture, but also highlighted the limitations of the gender bias imposed by both the official entity and the editorial practices of the time. By restoring the full names of the winners and acknowledging their participation in official disciplinary competitions, this research contributes to the construction of a more equitable architectural historiography and collaborates with the expansion of recognition of women’s contributions to 20th-century architecture.